Polyethylene Degradation by Plastivores Greater Wax Worms Larvae (Galleria mellonella) - Khlaif, Abbas T.; Abdulhay, Hind Suhail (Iraqi Journal of Science, 2023)
In this study, wax worm larvae (Galleria mellonella) were used to examine their ability to degrade and assimilate polyethylene (PE) as an energy source. This idea came from the similarity of wax, that is used as the sole diet for larvae, with PE in composition. Morphology changes, weight loss, FTIR analysis and GC-Mass test were studied to prove the degradation of PE by G. mellonella. The maximum depth of holes on the plastic surface and 16% PE weight loss was due to extensive cutting. The creation of a novel O-H stretching alcohols/phenols group absorbance peak at 3293cm-1 observed in wax worm larvae PE frass samples may be due to the oxidation in their gut. Accordingly, the biodegradation of PE by wax worm larvae is ensured.